SOCIAL INTERACTIONS WITH TUNAGRAHITA CHILDREN AT SLB YPAC PALEMBANG - Natasya Rifda Hanifah; Winda Agustia Anggarini; Alya Rizky Nur Kamila Wagiman; Hanna Azzahra Nabella; Yustika Pratiwi; Yudi Latama; Syelina Rizki Tria Umami; Ghaliyatul Ningtyas; Muhammad Feriyansyah; Regina Athia Mayalianti; Cherlin Vinanditha; Nindy Alfatikhatus Salamah; Raudhatul Fauziah; Artika Adi Prasetiani; Chairani (Journal of Islamic Psychology and Behavioral Sciences, 2023)
This research was conducted to find out the social interactions of mentally retarded children while they were at the Palembang Special School for the Development of Disabled Children (SLB YPAC). The research method used is a qualitative research method with data collection techniques through interviews and observation. The subjects in this study were four grade C junior high school students at SLB YPAC Palembang, namely MS, M, A and K. Based on the results of the study it can be concluded that the way of social interaction for mentally retarded children is the same as the way of social contact and communication in accordance with the conditions of social interaction.